Caracterização microestrutural e comportamento mecânico de aço fundido com composição química base (0,07% C; 8% Mn) para efeito TRIP - Reyler Bueno Faria (2017)
The alloyed castings steels represent materials with high potential for application in various segments. In this work was analyzed the microstructural characteristics and the mechanical behavior of an alloy steel with 0.07% by weight carbon and 8.1% by weight of manganese obtained by the casting process. The alloy was melted in electricinduction furnaces with crucibles with capacity of 20 kg and 110 kg of liquid steel. The tests were performed in the melting shop of the Serviço Nacional de Fundição de Aprendizagem Industrial - SENAI Itaúna Centro Tecnológico de Fundição Marcelino Corradi CETEF. They were performed during melting additions of ferroalloys, in addition also the temperature control and atmosphere of the bath liquid using argongas. The blocks of Keel type were pouring according the standard American Society for Testing and Materials - ASTM A781/2014. After the casting step, the blocks were heat treated for homogenization and standardization. Then was realized chemical analyzes were performed by optical emission spectrometry. The structures were characterized by macrography technique, optical microscopy, scanning electron microscopy and diffraction of x-rays. The mechanical properties were determined across tensile tests and microhardness. The characterized structure consisted of bainite and martensite with hardness of 342 ± 8.9 HV and 456 ± 6.2 HV, respectively. The grain sizes decreased significantly after the normalizing heat treatment at the two samplingconditions. In the as cast condition removed from the Keel block, the average grain size was 314 ± 164 m. In the normalized sample the size decreased to 24 ± 6.2 m. In the heat treated sample obtained in cast steel in the furnace with a capacity of 110 kg the average grain size was 19.6 m ± 5.0 m. In the analyzed samples of the blocks, the results were: as cast 128.5 ± 38.1 m and normalized 12.7 ± 3.8 m. Themechanical tensile strength of the casting specimens melted in induction furnace with a capacity of 20 kg and removed from the Keel block was 218 MPa in the as cast condition and 606 MPa in the heating treated condition. Both showed no elongation. In the blocks the results were 591 MPa and 1393 MPa under the as cast conditions and normalized, respectively. The "treated block" test specimen had a 3.5% elongation and 4% reduction in area. The tensile strength of the test specimen casting in furnace with 110 kg capacity, removed from the Keel block and heat treated, were lower than those obtained in the 20 kg melt. By scanning electron microscopy analysis, it was possible to verify intergranular fractures and the presence of aluminum oxides and manganese sulphides. By the macrography the presence of oxide films was identified